Pola Komunikasi Sosialisasi dan Perlindungan Hukum Anak terhadap Kasus Kekerasan pada Anak di Kabupaten Sumbawa - Iman, Topan Rahmatul; Siswadi, Imran; Yuliadi, Imam; Supriad, Supriad; Kurnia SF, Aka (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The definition of children differs in terms of age, for example, the Republic Indonesia Constitution no. 23 2002, children mean a person who has not reach the age of eighteen, and the one who is still in the womb. The commission of Indonesian Child Protection releases data about the child abuse in Indonesia from 2016 to 2020 that there are 3,824 cases of child as a victim of child abuse and facing the law. In Sumbawa itself, the total cases of child abuse are still high. This problem is reason why the Faculty of Social and Political Science Sumbawa University of Technology lecturers conduct a community service. This program was held in Sumbawa, particularly in the ballroom of Culture and Education Office of Sumbawa. The method in conducting the program was focus group discussion with the total participants of 15 people consisting of teachers of BK who teach in senior high school and the students who study in the high school. The results of the community service show that the causes of child abuse in Sumbawa are the overuse of gadget, parenting issue, stress, porn, and toxic relationship. The solutions that can be taken to prevent and solve the problem are communicating with child using psychology, sociology, and religious approach. Also, a program such as “ Satgas Anti Galau” can be implemented in school as the platform for students to have a consultation.